Effect of anisotropy on the mechanical testing of Ni-based single-crystal superalloys - Polatoğlu, C (2023)
With the objective of generating the maximum energy possible from a given fuel supply, both the aerospace and power generation sectors are engaged in a continuous endeavour to enhance the efficiencies of gas turbine engines. Elevating the turbine entry temperature (TET) theoretically promises improved performance; but material limitations restrict the extent to which this can be achieved. Ni-based single-crystal superalloys, renowned for retaining their high yield strengths at extreme temperatures, have been created to break these boundaries. In this thesis, we investigate the mechanical properties of the Ni-based single-crystal superalloy STAL15 from three distinct angles.